2011
DOI: 10.4103/0970-4388.90746
|View full text |Cite
|
Sign up to set email alerts
|

Clinical application of palatal lift appliance in velopharyngeal incompetence

Abstract: The presence of nasal air leak in cleft palate patients with velopharyngeal incompetence leads to characteristic nasal snort. The efficacy of the palatal lift appliance in patients with adequate velopharyngeal tissue with incompetence was tested. Speech quality improved after the wearing of palatal lift appliance. Palatal lift appliances are simple and efficient in reducing the nasal air leak. Ongoing speech therapy is necessary and advised for patients receiving palatal lift.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
6
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 1 publication
1
6
0
1
Order By: Relevance
“…The mechanical obstruction of the flow of air to the nasal cavity increased the oral pressure and improved the balance between the oro-nasal combinations of resonance, therefore; helped recovering the speech orality. These findings are also in agreement with previous studies [20, 21]. …”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The mechanical obstruction of the flow of air to the nasal cavity increased the oral pressure and improved the balance between the oro-nasal combinations of resonance, therefore; helped recovering the speech orality. These findings are also in agreement with previous studies [20, 21]. …”
Section: Discussionsupporting
confidence: 94%
“…The selection of abutment teeth, to retain the PLA, should be carefully evaluated in order to give maximum advantage to the lift. Posterior teeth act as the most appropriate abutments because they are closer to the cantilever extension [20]. Therefore, maxillary 1 st molars were chosen to receive Adam's clasps or C-clasps for all cases participated in this study.…”
Section: Discussionmentioning
confidence: 99%
“…4,6,7 Premkumar S reported the use of removable palatal lift appliance in a 9 year old patient with chief complaint of nasal speech and history of surgically repaired cleft palate. 8 Raju H et al 4 and Aboloyoun AI et al 9 conducted studies to assess the effectiveness of palatal lift appliances in patients who had previously undergone surgery for cleft palate in different age groups (16e26 years and 8e10 years respectively). The results of both the studies showed significant improvement in speech after treatment with a palatal lift appliance.…”
Section: Discussionmentioning
confidence: 99%
“…2 Maximum number of posterior abutments should be strategically used to avoid the disadvantages of cantilever. 3 The outcome of the treatment mainly depends on the efficacy of displacement of the soft palate, 8 degree of removal of compensatory articulations and the consistent production of target sound in normal conversational speech. 4,7 A well fabricated palatal lift appliance altogether prevents the air leakage from nostrils which imparts a beneficial effect on the speech therapy.…”
Section: Discussionmentioning
confidence: 99%
“…It is innervated by cranial nerve X (vagus nerve). Velopharyngeal movement also regulates oral and nasal activity and resonance during sound and respiratory flow . Velopharyngeal closure allows oral speech resonance for most phonemes and vowels, and the velopharynx opens for nasal resonance during production of nasal consonants /m/, /n/, and /ng/ .…”
mentioning
confidence: 99%